How psychosocial indicators push millennials to intend leaving their job: a study of generational differences in Iranian organizations - Sahraee, Rezvan; Abdullah, Haslinda; Bagherian, Fatemeh (University of Tehran, College of Farabi, 2021)
Nowadays, high voluntary turnover intention among Millennials has presented new challenges for organizations although it is unclear how the tendency to leave the organization has varied across generations and is significantly dominant among Millennials. This study aims to examine the effect of psychosocial factors including value, attitude, subjective norm, and perceived behavioral control on turnover intention, and specifically targets Iranian generations since they have been studied less in the workplace. The current study employed a descriptive cross-sectional survey procedure and randomly sampled 498 full-time workers from a large automotive company in Tehran. The direct assessment of the association between variables showed that extrinsic value has a significant and positive effect on turnover intention while the intrinsic value is not significantly associated with turnover intention. However, indirectly, intrinsic value orientation significantly contributes to a low turnover intention through the mediating effect of attitude, subjective norm, and perceived behavioral control, and extrinsic value is related to a high turnover intention through attitude and subjective norm but not through perceived behavioral control. Eventually, multi-group analysis revealed that the strength and direction of the relationship between value and turnover intention differ depending on generational cohorts in an Iranian social context.